Long-range order in linear ferromagnetic oscillator systems. Strong pair quadratic n-n potential - Skrypnik, W.I. (Український математичний журнал, 2004)
Long-range order is proved to exist for lattice linear oscillator systems with ferromagnetic potential energy containing a term with strong nearest-neighbor (n-n) quadratic pair potential. A contour bound and a generalized Peierls argument are used in the proof. Доведено, що далекий порядок існує у ґратковій системі лінійних осциляторів з феромагнітною потенціальною енергією, яка містить доданок із сильним парним квадратичним потенціалом взаємодії близьких сусідів (б-с). При доведенні використовуються контурна нерівність та узагальнений аргумент Пайєрлса.